1989
DOI: 10.1073/pnas.86.21.8338
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of an inhibitory insulin-like growth factor (IGF) binding protein from bone cell-conditioned medium: a potential local regulator of IGF action.

Abstract: Inhibitory insulin-like growth factor binding protein (In-IGF-BP) has been purified to homogeneity from medium conditioned by TE89 human osteosarcoma cells by two different methods using Sephadex G-100 gel filtration, FPLC Mono Q ion-exchange, HPLC C4 reverse-phase, HPLC CN reverse-phase, and affinity chromatographies. In-IGF-BP thus purified appeared to be homogeneous and unique by the following criteria. (i) N-terminal sequence analysis yielded a unique sequence (Asp-Glu-Ala-Ile-His-Cys-Pro-Pro-GluSer-Glu-Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
127
1
3

Year Published

1996
1996
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 331 publications
(142 citation statements)
references
References 31 publications
11
127
1
3
Order By: Relevance
“…Although its physiological role is still unclear, IGFBP-4 appears to inhibit IGF mitogenic actions under most experimental conditions, suggesting that it is an important negative regulator of cellular proliferation (17,53). A major factor regulating IGFBP action is its distribution between the soluble phase (interstitial fluid) and the extracellular matrix (ECM) or cell surface; inhibitory effects of IGFBP on IGF action are associated typically with high-affinity soluble forms.…”
Section: Discussionmentioning
confidence: 99%
“…Although its physiological role is still unclear, IGFBP-4 appears to inhibit IGF mitogenic actions under most experimental conditions, suggesting that it is an important negative regulator of cellular proliferation (17,53). A major factor regulating IGFBP action is its distribution between the soluble phase (interstitial fluid) and the extracellular matrix (ECM) or cell surface; inhibitory effects of IGFBP on IGF action are associated typically with high-affinity soluble forms.…”
Section: Discussionmentioning
confidence: 99%
“…The growth-promoting activity of IGF-I is determined not only by the concentration of IGF-I but also by the amounts of various IGFBPs (21,22). Of these, IGFBP-3 is the major binding protein (23).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to IGFBP-4, which exerts exclusively inhibitory actions on bone cells both in vitro (Mohan et al 1989(Mohan et al , 1995b and in vivo (Miyakoshi et al 1999), IGFBP-5 was identified as a stimulator of osteoblast mitogenesis (Andress & Birnbaum 1991, 1992, Bautista et al 1991, Andress et al 1993, Mohan et al 1995b). The stimulatory Schmid et al (1996) i=inhibition; s=stimulation; TSH=thyroid-stimulating hormone.…”
Section: Bone Physiology and Pathologymentioning
confidence: 99%